Enological-tourism Communication by Internet - Matellanes Lazo, Mónica (2011)
The use of the Internet bursts in a key moment for the enological tourism development in several regions of Spain and, it is essential to get to know and control the use of this new channel’s elements to communicate in an efficient way the strategical plans of enological tourism management towards different audiences. This research uses a comparative questionnaire about the management between the main enologicaltourism websites of two important origin denominations: La Rioja and Ribera del Duero. Like that, we’ll be able to analyze and reflect about different communication strategies which use every wine region to obtain more tourists and economic benefits.